TINDAK PIDANA DALAM MASA PEMBIAYAAN PERJANJIAN LEASING DITINJAU DARI PASAL 372 DAN PASAL 378 KUHP DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG FIDUSIA (Studi Kasus di Wilayah Polsekta Pontianak Selatan) - ANUAR SYARIFUDIN, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2012)
AbstractVehicle transfer in a period of payment of agreement of defrayal of leasing digressing from contents of agreement can be qualification as embezzlement crime as arranged Section 372 and deception crime as arranged Section 378 Criminal Law if fulfilling second element of Section Criminal Law is intended. This thing is related to agreement clause of standard giving freedom to the side of Creditor to submit law demands to Debitor is fore part other justices is it doesn't matter also thought well of by creditor pursuant to applicable law. According to its practice Agreement of Defrayal of Consumer also is bound with guarantee Fidusiary. Related to it, hence evaluated from invitors Law Number 42, 1999 About Fiduciary, fiduciary owner has rights prevention to take redemption of receivable of its receivable to result of execution of object becoming Fiduciary Guarantee Object. Its consequence, in the case of Pengalihan vehicle in a period of payment of agreement of defrayal leasing, hence creditor and Fiduciary Owner can crime the side of Debitor based on Section 36 expressing :